Analisis Kualitas dan Penerapan Software Quality Assurance pada Web K24klik Menggunakan Model ISO/IEC 9126 - -, Rendy Swanda Narastu; Sadarman Zai; Viktor Handrianus Pranatawijaya; Widiatry (ProTekInfo(Pengembangan Riset dan Observasi Teknik Informatika), 2024)
The purpose of this research is to evaluate the implementation and quality analysis of Software Quality Assurance (SQA) on the K24KLIK website using the ISO/IEC 9126 Model, as well as to study the concepts of software quality, SQA, and the ISO/IEC 9126 model, and to collect data through direct observation, document analysis, and direct testing of the website. After the data was collected, software features such as functionality, reliability, usability, efficiency, and portability were assessed. The results show that K24KLIK performs well in some respects, but performance, user experience, and reliability still need to be improved. SQA improves software quality, but requires constant supervision and evaluation and continuous improvement. So, to improve the quality of K24KLIK software, improvements and optimizations need to be made.